MOTIVASI KERJA DAN KINERJA ALUMNUS AKPER ADI HUSADA YANG BEKERJA DI RS ADI HUSADA UNDAAN WETAN SURABAYA - Ni Putu Rusmini (STIKes Adi Husada, 2015)
Education and development of the nurse is one of the activities to be carried out by the nursing managers to support the performance of nurses, that are expected to improve the quality of nursing care. The performance assessment is a tool that can be trusted in the control of human resources and productivity. The aim of this study was to identify the motivation to work and work performance of AKPER Adi Husada Surabaya ex-students who worked at the Adi Husada Undaan Wetan Hospital and identify relationship between both factors. This study uses correlation design with cross sectional approach, using consecutive sampling technique and obtained a sample of 94 respondents. Data obtained by using questionnaires and result was tested with Spearman Rank test using computer software with a significance p=0.05. Statistical test results showed r = 0.443, it shows the null hypothesis was rejected so that there was a weak relationship between motivation and work performance AKPER Adi Husada Surabaya ex-students who worked at the hospital Adi Husada Undaan Wetan Surabaya. So motivation factor was not the main factor that causes an increase in performance, but the entire internal and external factors greatly affect the performance of individual nurses. Expected nurses can improve motivation and other factors related to the performance becomes more optimized and can improve the quality of nursing care. Pembinaan dan pengembangan terhadap perawat merupakan salah satu kegiatan yang harus dilakukan oleh kepala ruangan atau manajer keperawatan untuk mendukung kinerja perawat, sehingga diharapkan mampu meningkatkan mutu pelayanan keperawatan. Penilaian kinerja merupakan alat yang dapat dipercaya dalam mengontrol sumber daya manusia dan produktivitas. Tujuan dari penelitian ini adalah untuk mengidentifikasi motivasi kerja, kinerja alumnus AKPER Adi Husada Surabaya yang bekerja di RS Adi Husada Undaan Wetan dan hubungan kedua faktor tersebut. Penelitian ini menggunakan desain korelasi dengan pendekatan potong lintang, menggunakan teknik consecutive sampling dan didapatkan sampel sebanyak 94 responden. Data diperoleh dengan menggunakan kuesioner kemudian diuji dengan Spearman Rank test menggunakan software computer dengan signifikansi p=0,05. Hasil uji statistic menunjukkan r= 0,443, hal tersebut menunjukkan hipotesis nol ditolak sehingga ada hubungan namun bersifat lemah antara motivasi kerja dan kinerja alumnus AKPER Adi Husada Surabaya yang bekerja di RS Adi Husada Undaan Wetan Surabaya. Faktor motivasi kerja bukan faktor utama yang menyebabkan peningkatan kinerja namun seluruh faktor internal maupun ekternal individu sangat mempengaruhi kinerja perawat. Diharapkan perawat dapat meningkatkan motivasi kerja dan faktor lain yang terkait sehingga kinerja menjadi lebih optimal dan dapat meningkatkan mutu pelayanan keperawatan. DOWNLOAD FULL TEXT PDF >>